The Effect of Green Investment, Eco-efficiency, and Carbon Emission Disclosure on Firm Value - Refika Afriani; Mellya Embun Baining; Puteri Anggi Lubis (Transpublika Publisher, 2026)
Growing apprehensions regarding environmental stewardship have amplified compulsory demands on corporations to assimilate conscientious practices into their operative strategies, particularly within capital markets that incorporate ethical and environmental screening criteria. This research aims to identify the bearing of green investment, eco-efficiency, and carbon emission disclosure on firm valuation among enterprises enumerated on the Indonesian Sharia Stock Index (ISSI) spanning the 2022–2024 period. A quantitative investigative approach with purposive sampling was employed, yielding 45 observations from 15 companies across three years. Ancillary data were procured from annual reports and sustainability reports and scrutinised through panel data regression utilising EViews 12. The empirical outcomes divulge that green investment exerts a propitious and consequential bearing on firm value, whereas eco-efficiency manifests a deleterious and statistically significant effect, intimating that market participants construe environmental efficiency undertakings as transient fiscal encumbrances rather than enduring value catalysts. Carbon emission disclosure demonstrates an affirmative yet inconsequential bearing on firm value. Concurrently, the three variables conjointly and substantively impinge upon firm value. These findings augment the burgeoning compendium of literature on sustainability conduct and firm valuation within the purview of Islamic capital markets, proffering empirical elucidations germane to investors, practitioners, and policymakers operating within Sharia-compliant investment frameworks.